Public participation in the process of EIA intentions of wind power plants in the Czech Republic - Schneider, Jiří; Mudra, Petr; Kozumplíková, Alice (Mendelova univerzita v Brně, 2018)
Public participation in decision-making process is an important function of the process called Environmental Impact Assessment (EIA). The respect for the public right in the participation of environmental impact assessment and the right to information are generally controlled by non-governmental organizations (NGOs) in cooperation with the Ministry of Environment. The support of public is provided in the cases in which queried entity tries not to give the requested information in the appropriate range. NGOs do not follow how the public is involved in the EIA process, and how the comments are relevant or incorporated and whether the final standpoint is influenced. This standpoint is not monitored by Czech Statistical Office. The article deals with the involvement of the general public in the EIA process of wind power plants in the Czech Republic. In selected regions (Moravskoslezský, Olomoucký, Ústecký and Jihomoravský), not only the quantity but also the relevance of the comments in relation to the outcome of the process are evaluated. The own typology groups of the public (individuals, petitions, self-government etc.) and also applying comments (noise, nature protection, administrative mistakes etc.) were used for the evaluation. All intentions obtained concurring standpoints in the case of zero or low interest of the public.
Keywords: Aarhus convention; Environmental impacts; Renewable sources; Wind energy